ASPECTS OF WORK AND MAIN ACHIVEMENTS OF THE LABORATORY OF BREEDING AND SEED PRODUCTION OF CUCURBITS CROPS - I. B. Korotseva (Ovoŝi Rossii, 2015)
In this article, the main stages of establishment and development of the laboratory of breeding and seed production of cucurbits crops since 1921 are presented. More than 50 varieties of cucurbits crops were developed. Research envelopes and main achievements of the laboratory in field of production of high yielding varieties of cucumber, pumpkin, and squash resistant to biotic and abiotic stresses are discussed.